A Strategic Analysis of China’s Semiconductor Supply Chain - ZHENG JUNXIONG (International Journal of Multidisciplinary Research and Studies, 2023)
In the emerging hi-tech cold war, the United States government's chokepoint policy is to limit China's access to cutting-edge semiconductor technology. It is becoming increasingly important for China's future development that it establish an indigenous semiconductor supply chain. This section details China's policies and growth in the semiconductor industry, and assesses the strengths and weaknesses of major Chinese companies in the IC supply chain. Strategic supply chain analysis reveals that China's semiconductor sector is robust despite pressure from the United States.